Exchangeable exchange shares of securities - Vigil Oliveros, Enrique (2018)
The purpose of this report is to analyze the exchange and extra-exchange actions, which derive from a security, this is done with the purpose of knowing what types of shares the holder can exercise in case of default. Any security title that contains the exchange relationship may go through the Single Execution Process, if it does not possess it, it will go through another judicial route. In other words, the holder will never lose the power to claim the primitive obligation, but it will depend on which way he should go, since our legislation favors the legitimate creditor of any abuse of right.